Transportation Mode Selection Preferences for Persons with Disabilities in the Disability-Friendly City of Yogyakarta - Azzahra, Fikakurrahni; Werdiningtyas, Rr. Ratri; Widodo, Candraningratri Ekaputri (Journal of Geosciences and Environmental Studies, 2024)
A disability-friendly city is a city that meets all the needs of people with disabilities according to service standards in education, health, employment, rehabilitation, social needs, and transportation. The Yogyakarta City Government has declared itself as a ‘Disability Friendly City’ since 2015. To fulfill the movement needs of people with disabilities, the Yogyakarta City government provides mass public transport, Trans Jogja. In addition to Trans Jogja, there are other modes, namely Difa Bike, two-wheeled private, public transportation, four-wheeled private, public transportation, and private vehicles. This study aims to determine the transportation mode selection preferences for persons with disabilities in Yogyakarta City as a Disability Friendly City. This study uses multiple linear regression analysis to determine the factors influencing persons with disabilities in choosing transportation modes. This study's findings state that most people with disabilities prefer private vehicle modes based on influential factors: travel destination, travel distance, travel time, transportation costs, and vehicle ownership.